Rotavirus y adenovirus en niños menores de 5 años como agente etiológico de enfermedad diarreica aguda en el barrio Pasallal cantón Calvas. - Ávila, Lady Mariuxi (2013)
Acute diarrheal diseases (EDA) are abrupt onset, characterized by the presence of four or more bowel movements a large liquid component manifests with abdominal pain, vomiting , nausea and occasionally fever can be caused by viruses , bacteria or parasites , affecting the vast majority of the child population , is little known in many people how to prevent these diseases. The importance of this research is to establish current data and real people going through a process in the gastrointestinal infectious viral etiology. Reason for proposed study Rotavirus and Adenovirus as an etiological factor of acute diarrheal diseases , identify the most relevant risk factors for their development and assess the percentage of Rotavirus and Adenovirus that are causing EDA , we conducted a study descriptive and cross- border section of the Canton Neighborhood Pasallal Bald with a sample of 51 children under 5 years by immunochromatographic rapid tests for Rotavirus and Adenovirus in feces identifying risk factors through a survey , reaching the following conclusions : That the majority of the children studied were not present Adenovirus, Rotavirus 8% and 92 % other etiologic agents , through the survey found that 100 % of the population does not have basic sewage services (latrines ) , drinking water , 90 % use river water for consumption , 78 % do not boil water before drinking , 24% do not wash before consuming food and poorly implemented the standards of personal hygiene , 96% no is immunized and finally through a talk spread the results of research and spoke about the importance of prevention and management of hygiene measures to prevent the EDA . Keywords: EDA , Children , Adenovirus , Rotavirus , Immunochromatography